FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG (Studi Empiris Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Saleh Saleh; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the factors that influence audit report lag. The population in this study is a manufacturing company listed on the Indonesian stock exchange. The technique used in sampling is purposive sampling technique, the sample chosen was 30 companies. Data is taken using the documentation method. The data analysis method used is multiple regression analysis with the help of SPSS version 16 software (Product Statistics and Solution Services version 16). The test data used is the simultaneous hypothesis test (f), determination coefficient (R2), and partial hypothesis test (t). The results of the study indicate that simultaneously the independent variables significantly influence the dependent variable. Based on the test results of the coefficient of determination, the value of R square is 32.9% while the remaining 67.1% is influenced by other variables not included in this study. Based on the results of the partial test the profitability variable does not affect audit report lag, solvency does not affect audit report lag, audit opinion does not affect audit report lag, company size has a positive effect on audit report lag.Keywords: profitability, solvency, audit opinion, company size